2005
DOI: 10.1002/pmic.200402107
|View full text |Cite
|
Sign up to set email alerts
|

Web‐based data warehouse on gene expression in human colorectal cancer

Abstract: Based on biomedical literature databases, we tried a first step for constructing a gene expression "data warehouse" specific to human colorectal cancer (CRC). Results of genome-wide transcriptomic research were available from 12 studies, using various technologies, namely, SAGE, cDNA and oligonucleotide arrays, and adaptor-tagged amplification. Three studies analyzed CRC cell lines and nine studies of human samples. The total number of patients was 144. Out of 982 up- or down-regulated genes, 863 (88%) were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Meta-analyses have been done previously to determine differentially expressed genes in colorectal cancer (1,9,10). However, these studies and others usually do not consider whether the level of overlap observed is statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses have been done previously to determine differentially expressed genes in colorectal cancer (1,9,10). However, these studies and others usually do not consider whether the level of overlap observed is statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Although an abundance of data comparing the expression profiles of cancerous to normal tissue has been generated, to date, no reliable biomarker has resulted. One explanation for this lack of translational success to the clinic has been the inconsistency in the results of independent studies (1,9,10). Explanations for this low overlap include utilization of different tissue resection methods (microdissection, laser capture microdissection, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, genomics-and proteomicsbased approaches have been used to identify new biomarkers for CRC. Particularly 2-DE has been used in many of the proteomics studies (11). Despite a number of limitations, the resolution of 2-DE gels is impressive, rendering this technology still a preferred tool in many proteomics studies (12).…”
mentioning
confidence: 99%
“…Despite a number of limitations, the resolution of 2D gels is impressive, rendering this technology still a preferred tool in many proteomics studies [15]. Along with 2DE, two technical methods often applied in the research of serum proteomics include: Surface enhanced laser desorption and ionization time-offlight mass spectrometry (SELDI-TOF-MS) and Matrix assisted laser desorption/ ionization time-of-flight mass spectrometry (MALDI-TOF-MS).…”
Section: Introductionmentioning
confidence: 99%